Translation and its fictions: pseudotranslation and partial cultural translation in focus - (:unkn) unknown (Taylor & Francis, 2023)
This article asks whether and what differences exist between the notions of pseudotranslation and partial cultural translation. Although they are both ultimately untranslated texts, their respective definitions acknowledge the possibility that each category may be taken as a translation. To answer its research question, the article examines the distinctive features of pseudotranslation and partial cultural translation across three primary sources that showcase traits common to both categories. First, the analysis sets these two notions against the backdrop of a fictional subtext which informs translation theory, demonstrating how pseudotranslation and partial cultural translation feed into this subtext. It then goes on to investigate the function of paratexts and culture-specific items in the three primary sources. Finally, the article identifies the different intentions underpinning pseudotranslation and partial cultural translation: while the former explicitly aims to be perceived as a translation, the latter is not written to be consumed as a translated text.
Keywords: Pseudotranslation, partial cultural translation, fictions of translation, paratexts, culture-specific items; Identities in Transformation; Modern Italian writers; Translation; Translation studies